Holistic approach to adaptive reuse research focused on the design strategy and its extended categories: lessons from a critical review - Yoon-Jeong Shin; Eun Joo Park; Eunki Kang (Journal of Asian Architecture and Building Engineering)
Despite recent increases in adaptive reuse practices and research, issues such as a lack of mutual supplementation between practice and research for implementing successful design strategies remain ongoing problems. Consequently, research is necessary to establish a comprehensive roadmap for future adaptive reuse research and practice through a critical review of existing research, identifying recent trends and limitations. This paper employed the PRISMA-ScR checklist in adopting a scoping review approach and selected 91 articles for preliminary review and 32 for in-depth review. It focuses on adaptive reuse design strategies but extends the scope to relevant areas, providing a more comprehensive and insightful outlook. The selected articles were classified into four categories: (1) theoretical development and recent trends, (2) decision-making, (3) design strategy, and (4) evaluation. The research identified that an in-depth research plan related to each scope is needed, including a thorough analysis of existing buildings, an integrated strategy based on establishing a conceptual framework, and the selection of credible and customized evaluation criteria. Most importantly, a holistic and integrated perspective on the complementary relationships between adaptive reuse scopes is needed. This study assists in formulating adequate research directions and appropriate design strategies for successful adaptive reuse practices.